Feminist Collections, v.15, no.2 (winter 1994) - (:unkn) unknown (My University, 1994)
Subtitle: A Quarterly of Women's Studies Resources. 46p.
FROM THE EDITORS. BOOK REVIEWS: WOMEN'S WORK IN THE INTERNATIONAL MARKETPLACE by Sharon Tiffany.[Review of] Tahitian Transformation: Gender and Capitalist Development in a Rural Society by Victoria S. Lockwood; Zapotec Women by Lynn Stephen; Let the Good Times Roll: Prostitution and the U.S. Military in Asia by Saundra Pollock Sturdevant and Brenda Stoltzfus; and Factory Daughters: Gender, Household Dynamics, and Rural Industrialization in Java by Diane Lauren Wolf. UNDISPUTED WOMANHOOD, UNCROWNED GLORY: AFRICAN AMERICAN WOMEN AND THE LITERARY EXPERIENCE by Anthonia Kalu.[Review of] The Unforgetting Heart: An Anthology of Short Stories by African American Women 1859- 1993 ed. by Asha Kanwar; Wild Women Don't Wear No Blues: Black Women Writers on Love, Men and Sex ed. by Marita Golden; and Written By Herself: Literary Production by African American Women, 1746-1892 by Frances Smith Foster. OUT IN THE MAINSTREAM: FINDING THE LESBIANS IN POPULAR CULTURE by Joan Ariel.[Review of] Gay and Lesbian Plays: An Annotated Bibliography by Ken Furtado and Nancy Hellner; Outwrite: Lesbianism and Popular Culture by Gabriele Griffin; Ladyslipper Catalog & Resource Guide: Recordings by Women; Facets Gay & Lesbian Video Guide by Patrick Z. McGavin; An Encyclopedia of Gay and Lesbian Recordings by Jay McLaren; Gays and Lesbians in Mainstream Cinema by James Robert Parish; Contemporary Lesbian Writers of the United States ed. by Sandra Pollack and Denise D. Knight; Gay and Lesbian Characters and Themes in Mystery Novels by Anthony Slide; and Women's Music Plus: Directory of Resources in Women's Music & Culture. A VISITOR FROM ABROAD: A DUTCH WOMEN'S STUDIES LIBRARIAN IN THE US by Gusta Drenthe. GOPHERING AROUND IN WOMEN'S STUDIES by Phyllis Holman Weisbard. FEMINIST PUBLISHING: A Canadian press celebrates twenty-five years of publishing; the last feminist print shop in North America succumbs; and a new feminist press starts up in New Mexico. PRESS GANG PRINTER: THE PRESSES STOP by Agnes Huang. COMPUTER TALK: Databases, email lists, electronic journals, and other resources. RESEARCH EXCHANGE. NEW REFERENCE WORKS IN WOMEN'S STUDIES: Women spies; Islamic women; US. women's research centers; women in paid employment; international gender roles; women with HIV/AIDS; psychology; women's studies in Europe and in India; modem American women writers; quotations from Black women; female detectives; gay and lesbian periodicals; plus an A - Z desk reference on women. (Reviewed by Phyllis Holman Weisbard) PERIODICAL NOTES: New and newly discovered periodicals on South African women, literature, goddess stories, Jewish women, women in the southwest of England, menopause, midlife issues, women veterinarians, interdisciplinary studies, travel, law, Black women's health concerns, women with HIV/AIDS, women's health center management, general health concerns, and philanthropy. Special issues of periodicals on African American women's culture, feminists in international relations, women in management, women and children refugees, Canadian women writers, writer Samuel Johnson and gender. Ceased publication: WLW Journal and Healthsharing. Transitions: Isis Wicce moves from Switzerland to Uganda. (Compiled by Linda Shult) ITEMS OF NOTE: A report on women faculty in the classroom, an international overview of women's health, a brochure on women and free trade, an environmental program for women, the Clarence Thomas hearing transcripts, an article on mentoring, a book dealer's catalog set, AARP's benefits outreach project, a phone-referral service for businesswomen, working papers from the Center for Research on Women, a new Japanese written-language character, a book on female genital mutilation, and a publication on African American women in the sciences.(Compiled by Renee Beaudoin) WISCONSIN BIBLIOGRAPHIES IN WOMEN'S STUDIES. BOOKS RECENTLY RECEIVED.
Keywords: Women's Studies; Gender; Feminism; Library Resources; Reviews